When Children Draw Gods: A Multicultural and Interdisciplinary Approach to Children's Representations of Supernatural Agents - Brandt, Pierre-Yves; Dandarova, Žargalma; Cocco, Christelle; Vinck, Dominique; Darbellay, Frédéric (New Approaches to the Scientific Study of Religion, 2023)
This open access book explores how children draw god. It looks at children’s drawings collected in a large variety of cultural and religious traditions. Coverage demonstrates the richness of drawing as a method for studying representations of the divine. In the process, it also contributes to our understanding of this concept, its origins, and its development. This intercultural work brings together scholars from different disciplines and countries, including Switzerland, Japan, Russia, Iran, Brazil, and the Netherlands. It does more than share the results of their research and analysis. The volume also critically examines the contributions and limitations of this methodology. In addition, it also reflects on the new empirical and theoretical perspectives within the broader framework of the study of this concept. The concept of god is one of the most difficult to grasp. This volume offers new insights by focusing on the many different ways children depict god throughout the world. Readers will discover the importance of spatial imagery and color choices in drawings of god. They will also learn about how the divine's emotional expression correlates to age, gender, and religiosity as well as strategies used by children who are prohibited from representing their god